Community interventions for pandemic preparedness: A scoping review of pandemic preparedness lessons from HIV, COVID-19, and other public health emergencies of international concern. - Sali Hafez; Sharif A Ismail; Zandile Zibwowa; Nadin Alhamshary; Reem Elsayed; Mandeep Dhaliwal; Fiona Samuels; Ade Fakoya (PLOS Global Public Health)
Community action is broadly recognised as central to comprehensive and effective system responses to pandemics. However, there is uncertainty about how and where communities can be best supported to bolster long-term resilience and preparedness. We applied a typology of community interventions (Community Informing, Consulting, Involving, Collaborating or Empowering-or CICICE) to cover the diverse range of interventions identified across the literature and used this to structure a scoping review addressing three linked topics: (i) how CICICE interventions have been understood and applied in the literature on epidemic and pandemic preparedness; (ii) the spectrum of interventions that have been implemented to strengthen CICICE and (iii) what evidence is available on their effectiveness in influencing preparedness for current and future emergencies. We drew on peer-reviewed and grey literature from the HIV (from 2000) and COVID-19 pandemics and recent public health emergencies of international concern (from 2008), identified through systematic searches in MEDLINE, Scopus, the Cochrane Collaboration database, supplemented by keyword-structured searches in GoogleScholar and websites of relevant global health organisations. Following screening and extraction, key themes were identified using a combined inductive/deductive approach. 130 papers met the criteria for inclusion. Interventions for preparedness were identified across the spectrum of CICICE. Most work on COVID-19 focused on informing and consulting rather than capacity building and empowerment. The literature on HIV was more likely to report interventions emphasising human rights perspectives and empowerment. There was little robust evidence on the role of CICICE interventions in building preparedness. Evidence of effect was most robust for multi-component interventions for HIV prevention and control. Much of the reporting focused on intermediate outcomes, including measures of health service utilisation. We put forward a series of recommendations to help address evidence shortfalls, including clarifying definitions, organising and stratifying interventions by several parameters and strengthening evaluation methods for CICICE.